A novel method of collection of saliva for estimation of steroid levels in extremely premature infants. (21st January 2013) - Ng, Sze M; Drury, Josephine A; Turner, Mark A; Didi, Mohammed; Victor, Suresh; Newland, Paul; Weindling, A Michael
Abstract Aim The major advantage of salivary cortisol sampling is that it is considerably less invasive than taking a blood sample. However, previous methods of obtaining saliva in premature infants have been poorly tolerated and inaccurate. We describe a simple, non‐distressing technique for obtaining saliva samples to assess extremely premature infants' salivary cortisol status. Methods We prospectively obtained early morning saliva samples from extremely premature infants. Their gestational age ranged between 23 and 27 weeks. Saliva was obtained using four standard universal swabs by placing one swab at a time in the infant's mouth for 1–2 min. No salivary stimulants were used. Results There were 65 infants (36 males). Mean gestation was 25.3 ± 1.3 weeks. This technique had a success rate of 85% in obtaining a mean of 150 μL of saliva (range 50–350 μL) by trained staff. No adverse events were recorded. Conclusion We describe a novel, safe, non‐distressing and effective method of saliva collection for salivary cortisol measurement in extremely premature infants.